Taxonomic notes on the genus Laemoglyptus Fairmaire from Taiwan (Coleoptera, Cantharidae) - Hsiao, Yun; Pang, Hong (Zootaxa, 2017)
The lectotype and paralectotype of Laemoglyptus sauteri (Pic, 1911) are herein designated. The following taxonomic changes are proposed: Laemoglyptus sauteri (Pic, 1911) = L. atripes Pic, 1921, syn. nov. = L. rubrithorax (Pic, 1912), syn. nov. Additionally, L. sauteri is redescribed in detail and supplemented with photos of the habitus and female genitalia, illustrations of clypeus, aedeagus and ventrite VII of females, and the distribution map. A key for the identification of Laemoglyptus species from Taiwan is also included.